Characterizations of electrode geometrical shape for dielectrophoresis - N. Burham; A. A. M. Shahar; A. A. Aziz; T. N. T. Yaakub; N. Khairuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a characterization of geometrical shape on dielectrophoresis by determining and analysing the geometrical shape of electrodes. The structure or geometrical shape of dielectrophoresis electrode is design using COMSOL software to determine the maximum trapping efficiency of particles. The trapping efficiency of particles can be evaluated by analysing the best electrical gradient and investigated the behaviour of the particles if the existence of a non-uniform electric field.  There are three geometrical shapes have been designed which is, peel chain shape, castle wall shape and comb shape. Each of the geometrical shapes have different magnetic field produce, hence each of the design have specific application. Furthermore, these three designed are analysed by varying the material of the electrode for the best trapping efficiency. From the various and previous study, for maximum trapping efficiency the shape used is peel chain shape which is suitable for biological and non-biological particles separation. But for the castle wall and comb shape is the most suitable for biological particles such as red blood cell and bacteria trapping. As for the result obtain, it is proven that peel chain shape could achieve maximum electrical gradient to trap biological or non-biological particles in the future.